Pilates for improvement of muscle endurance, flexibility, balance, and posture - Kloubec, J. A. (The Journal of Strength and Conditioning Research, 2010)
Many claims have been made about the effectiveness of Pilates exercise on the basic parameters of fitness. The purpose of this study was to determine the effects of Pilates exercise on abdominal endurance, hamstring flexibility, upper-body muscular endurance, posture, and balance. Fifty subjects were recruited to participate in a 12-week Pilates class, which met for 1 hour 2 times per week. Subjects were randomly assigned to either the experimental (n = 25) or control group (n = 25). Subjects performed the essential (basic) mat routine consisting of ~25 separate exercises focusing on muscular endurance and flexibility of the abdomen, low back, and hips each class session. At the end of the 12-week period, a 1-way analysis of covariance showed a significant level of improvement (p <= 0.05) in all variables except posture and balance. This study demonstrated that in active middle-aged men and women, exposure to Pilates exercise for 12 weeks, for two 60-minute sessions per week, was enough to promote statistically significant increases in abdominal endurance, hamstring flexibility, and upper-body muscular endurance. Participants did not demonstrate improvements in either posture or balance when compared with the control group. Exercise-training programs that address physical inactivity concerns and that are accessible and enjoyable to the general public are a desirable commodity for exercise and fitness trainers. This study suggests that individuals can improve their muscular endurance and flexibility using relatively low-intensity Pilates exercises that do not require equipment or a high degree of skill and are easy to master and use within a personal fitness routine.